Qualitative and Quantitative Characteristics of Local Goats in Bangai Laut Regency - Wildan Radiansyah Sunani; Fahrul Ilham; Nibras K. Laya; Suparmin Fathan; Safriyanto Dako (Jambura Journal of Animal Science, 2026)
The purpose of this study was to determine the existence of local goat characteristics in Banggai Laut Regency. Research was conducted in June 2025 on Banggai Island, Banggai Laut Regency, Central Sulawesi Province. The research subjects were local goats, male and female, aged 1-2 years, from Banggai Island. Observation and interviews were used to determine the quantitative and qualitative characteristics of local goats. The variables studied included animal age, sex, body weight, and body measurements, including shoulder height, hip height, hip width, body length, chest width, chest depth, chest circumference, ear length, and ear width. The result show The qualitative characteristics of Kacang goats in Banggai Tengah District, Banggai Laut Regency, partly show the characteristics of a dominant brown coat color, a combination of color patterns often appears compared to a single color, one of which is black and white, ears are predominantly half hanging, have horns, a flat face line, a concave back line, and the majority are beardless. The average body weight of male goats is 20.83 ± 10.68 kg, shoulder height 53.48 ± 9.90 cm, hip height 54.75 ± 9.95 cm, body length 50.23 ± 7.62 cm, chest width 14.95 ± 3.28 cm, chest depth 25.64 ± 4.99 cm, chest circumference 64.57 ± 12.13 cm, hip width 16.07 ± 3.32 cm, ear length 14.41 ± 2.30 cm, and ear width 6.70 ± 0.91 cm. The average body weight of female goats is 19.23 ± 5.18 cm, shoulder height 50.82 ± 3.99 cm, hip height 52.31 ± 4.42 cm, body length 50.94 ± 4.88 cm, chest width 14.78 ± 1.92 cm, chest depth 24.45 ± 2.23 cm, chest circumference 63.43 ± 6.65 cm, hip width 16.42 ± 1.66 cm, ear length 13.52 ± 1.76 cm, and ear width 6.27 ± 0.71 cm. The body and morphometric size of Kacang goats in Banggai Laut vary, with males generally having larger body sizes than females, not significantly different from Kacang goat populations from various other regions in Indonesia.